PolB1 Is Sufficient for DNA Replication and Repair Under Normal Growth Conditions in the Extremely Thermophilic Crenarchaeon Sulfolobus acidocaldarius - Miyabayashi, Hiroka; Jain, Rupal; Suzuki, Shoji; Grogan, Dennis W.; Kurosawa, Norio (Frontiers in Microbiology, 2020)
The thermophilic crenarchaeon Sulfolobus acidocaldarius has four DNA polymerases (DNAPs): PolB1, PolB2, PolB3, and Dbh (PolY). Previous in vitro studies suggested that PolB1 is the main replicative DNA polymerase of Sulfolobales whereas PolB2 and Y-family polymerases Dpo4 (Saccharolobus solfataricus) or Dbh are involved in DNA repair and translesion DNA synthesis. On the other hand, there are various opinions about the role of PolB3, which remains to be clearly resolved. In order to examine the roles of the DNAPs of S. acidocaldarius through in vivo experiments, we constructed polB2, polB3, and dbh deletion strains and characterized their phenotypes. Efforts to construct a polB1 deletion strain were not successful; in contrast, it was possible to isolate triple gene-deletion strains lacking polB2, polB3, and dbh. The growth of these strains was nearly the same as that of the parent strains under normal growth conditions. The polB2, polB3, and dbh single-deletion strains were sensitive to some types of DNA-damaging treatments, but exhibited normal sensitivity to UV irradiation and several other damaging treatments. Overall, the genotype which exhibited the greatest sensitivity to the DNA-damaging treatments we tested was the ΔpolB2 ΔpolB3 combination, providing the first evidence of overlapping function for these two DNAPs in vivo. The results of our study strongly suggest that PolB1 is responsible for the DNA replication of both the leading and lagging strands and is sufficient to complete the repair of most DNA damage under normal growth conditions in S. acidocaldarius.